The Importance of Socio-Cultural Factors in the Development of Sociolinguistic Competence of Journalism Students - Khalikova Dildora Shakirjanovna (International Journal on Integrated Education, 2022)
The article deals with the issues based on analyzing the importance of socio-cultural factors in the development of sociolinguistic competence of journalism students. As we know, the society needs a specialist who not only has a high level of professionalism, social activity, demonstrates a creative, constructive attitude to his work, but also the ability to work in a team, adapt to change, share the values necessary to live in a complex democratic society, be its responsible citizen. In this article ethno-cultural and socio-cultural factors of the English language and the methodology of teaching a foreign language is considered, possible ways of the most effective resources for the formation of sociolinguistic competence in students of the specialty "journalism" are shown.